Understanding the Dynamics of Polymer Extrusion: Simulation of Thermoplastics Processing with Planetary Roller Extruders - Mario Radwan; Steffen Schneider; Thomas Ernst Müller; Sulamith Frerich (Heliyon, 2024)
Resource efficient processing of polymers is of paramount importance to minimize energy consumption, processing time, and material losses in the polymer industry. This study is concerned with polymer processing in planetary roller extruders. A three-dimensional numerical flow simulation was tailored to understand the polymer flow through the extruder in detail. Using the simulation software ANSYS Polyflow, we quantified both directly measurable process parameters, such as pressure build-up, and more intangible parameters, such as material shear. By varying operational and material parameters in a sensitivity analysis, we showed that the dynamics, material stress and pressure build-up are controlled primarily by the number of spindles and their rotational speed. Notably, this work provides the first successful validation of a 3D simulation of a polymer flow in a planetary roller extruder against actual experimental data. The simulation showed robust agreement between the simulated and experimental values, provided that a critical backpressure length is reached. This computational approach minimizes labor-intensive experimental testing in polymer processing.